Perbedaan Kepatuhan Anak Autis antara Applied Behavior Analysis (ABA) dan Aromaterapi Lavender - Hapsari, Eti Dwi; Nani, Desiyani; Fitriyani, Aris (Prodi Keperawatan Purwokerto, 2024)
Background: Autism is a developmental disorder that cannot be cured but its symptoms can be reduced with therapy. One therapy for autistic children is ABA behavioral therapy. The success of ABA behavioral therapy is greatly influenced by the level of compliance of autistic children. Disobedience in autistic children is influenced by the anxiety that occurs, this is because autistic children who are used to living in their world must carry out tasks in the ABA method of behavioral therapy. Lavender aromatherapy has been widely used to reduce anxiety. Lavender aromatherapy is expected to reduce anxiety levels thereby increasing compliance scores in autistic children. Objective: To determine the difference in compliance scores of autistic children when undergoing ABA behavioral therapy without and with lavender aromatherapy. Methods: The research was a post-test control group design. The sample consisted of 12 autistic children recruited using a purposive sampling method. The intervention is the ABA therapy with lavender aromatherapy made of 20 drops in 100 ml. The data were analyzed using the Wilcoxon difference test Results: The average compliance score for autistic children without aromatherapy was 34.54 ± 17.02, while the average compliance score for autistic children with aromatherapy was 46.76 ± 18.98 (z= 0.013, p= 0.05). The ABA with lavender aromatherapy effectively improves the compliance of autistic children. Conclusion: There was a significant difference between the compliance scores of autistic children when ABA behavioral therapy was carried out without and with lavender aromatherapy.